Environmental Regulation, Sentiment, and Eco-Innovation: Evidence From China - Sun, Yunpeng; Li, Haoning; Bao, Qun; Lu, Zhou (Frontiers in Environmental Science, 2022)
This study aims to shed light on the effects of environmental regulation on China’s eco-innovation driven by investor sentiment and public sentiment from 2003 to 2017. Adopting a text analysis technique and LSTM model, this study identifies the investor sentiment and public sentiment by online comments. We find that environmental regulation has a positive effect on China’s eco-innovation through public sentiment, whereas environmental regulation inhibits China’s eco-innovation through investor sentiment. Second, the regulatory tools of environmental regulation not only improve the public’s enthusiasm and awareness of environmental protection and eco-innovation in China but also bring the pressure to investor survival and continuous innovation. Third, we confirm that the environmental regulation has threshold effects on general public sentiment and investor sentiment for affecting China’s eco-innovation. Based on this result, environmental regulation easily triggers public sentiment for affecting China’s eco-innovation. Furthermore, in order to test whether environmental regulation has spatial spillover effect, by constructing the Spatial Durbin model, this study finds that the environmental regulation has spatial spillover effects on different regions’ eco-innovation in China through two kinds of sentiment. To the policy implication, this study from two kinds of sentiment to guide the environmental regulators would effectively improve the level of eco-innovation in China.